An Increasing Insulation Resistance of Poly Vinyl Formaldehid (PVF) Wire in Avoiding Voltage Breaking Electrical Installations - Sanpun Nobel Manalu; Adi Sastra P. Tarigan; Solly Aryza (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
The development of industry in Indonesia has experienced a fairly rapid capacity in recent years, in line with that, many problems have arisen. To overcome these problems, it is necessary to test the results of an industrial product in order to determine the properties of the materials produced so that the results of a product can be used in accordance with good standards and quality. Testing is also useful in preventing harm to humans and the surrounding environment caused by breakdown of cable insulation. So that repeated tests are very good in the selection of conductors to be used. Every industrial product material before being used as part of an equipment, for example for transformer coils, must be tested based on predetermined standards. This is so that the dielectric properties of these materials can be known from the test results, so a conclusion will be drawn whether the material is suitable for use or not.